Acute suppurative appendicitis associated with Enterobius vermicularis: an incidental finding or a causative agent? A case report - Boubacar Efared; Gabrielle Atsame-Ebang; Boubacar Marou Soumana; Layla Tahiri; Nawal Hammas; Hinde El Fatemi; Laila Chbani (BMC Research Notes, 2017)
Abstract Background Histological acute appendicitis patterns associated with Enterobius vermicularis is an extremely rare finding. The exact role of this parasite in acute appendicitis is controversial as usually resected specimens show no evidence of histological inflammation. Case presentation We present herein a case of a 21-year-old male Arabic patient who presented with clinical syndrome of acute appendicitis. Emergency appendectomy was performed and the histopathological examination of the resected specimen showed the presence of E. vermicularis as well as intense acute inflammatory patterns such as mucosal ulceration and suppurative necrosis. The post-operative course was uneventful and the patient was discharged with appropriate anti-helmintic drug prescription. Conclusion Acute appendicitis due to E. vermicularis is a very rare occurrence. The histopathological analysis of resected specimens should pay special attention to search for this parasite for adequate post-operative treatment of patients.